Chaos Rules Revisited - David Murphy (International Review of Research in Open and Distributed Learning, 2011)
About 20 years ago, while lost in the midst of my PhD research, I mused over proposed titles for my thesis. I was pretty pleased with myself when I came up with Chaos Rules (the implied double meaning was deliberate), or more completely, Chaos Rules: An Exploration of the Work of Instructional Designers in Distance Education. I used the then-emerging theories of chaos and complexity to underpin my analysis. So it was with more than a little excitement that I read the call for contributions to this special issue of IRRODL. What follows is a walk-through of my thesis with an emphasis on the contribution of chaos and complexity theory.